Lawsone as synthon in the catalytic asymmetric reactions. (16th July 2022) - Pasha, Mohammed Anif; Anebouselvy, K.; Ramachary, Dhevalapally B.
Abstract: Lawsone (2-hydroxy-1, 4-naphthoquinone) is a red-orange dye present in the leaves of the henna plant ( Lawsonia inermis ), one of the most important synthon for many branches of chemistry and biology. In the past two decades, it is undeniable that the lawsone chemistry has gained a lot of interest among synthetic organic chemists. Lawsone was utilized to construct structurally complex pharmaceutically active chiral molecules under the organo- and organometallic-catalysis. This review summarizes the most recent advances in the asymmetric synthesis of high-yielding, optically active functionally rich molecules utilizing lawsone and lawsone derivatives as key building blocks. Graphical abstract: Image 1